Analisis Kerusakan Tanah pada Lahan Sawah Berbasis Sistem Informasi Geografis di Kecamatan Kuta Utara Kabupaten Badung - Girsang, Giyo Brem Dana; Trigunasih, Ni Made; Arthagama, I Dewa Made (Agrotrop : Journal on Agriculture Science; Vol 14 No 2 (2024)DO - 10.24843/AJoAS.2024.v14.i02.p12, 2024)
Analysis of Soil Degradation in Rice Fields Based on Geographic Information System in North Kuta Subdistrict, Badung Regency. North Kuta district is one of the regions in the Badung district where a portion of the land is utilized as wilderness. The land productivity in North Kuta district is susceptible to degradation due to inconsistent land processing with conservation principles and the high transfer functions of the land. The research aims to assess the potential for land degradation, determine the status of land degradation, identify the distribution of soil degradation, and propose directions for treating land degradation in the wilderness areas of North Kuta district. The research employs a comparative descriptive method. By overlaying land-use maps, slope maps, and land type maps using geographic information systems, five homogeneous land units were identified. The observed land use consists of plains with field observations encompassing surface rocks and solum depth. Laboratory analysis of soil samples was conducted to determine weight contents, total porosity, texture, permeability, pH, electrical conductivity, and microbial count. The determination of degradation status is based on predefined criteria for land degradation. The research results indicate one class of potential soil degradation, specifically the potential for mild soil degradation. The potential for mild degradation is observed in Tibubeneng Village, Kerobokan Village, Kelod Village, Canggu Village, Kaja Village, and Dalung Village. The degradation status in the research area is mild, with porosity being a limiting factor in Changgu Village, Kerobokan, Kelod Village, and Dalung. Recommendations for improving the wilderness in the research area include providing organic material and implementing soil processing.